2005
DOI: 10.3208/sandf.45.2_109
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity Modeling of the Effect of Sample Preparation Method on Sand Response

Abstract: Experimental evidence shows that different preparation methods produce sand samples with distinctly different stress-strain response. This paper explores and draws conclusions from the measured differences on the monotonic undrained triaxial response of Toyoura sand, prepared by different methods at the same values of void ratio and initial effective stresses. This is achieved by comparing data and simulations performed with a recently developed plasticity constitutive model, which accounts for the effect of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 35 publications
0
24
0
9
Order By: Relevance
“…The subloading surface concept (Hashiguchi and Ueno, 1977) and the bounding surface concept (Dafalias and Popov, 1975) are the two popular methods that do this. Although use of bounding surface plasticity is widely documented in the broader geomechanics literature, there have been few papers in Soils and Foundations that have used this concept (e.g., Papadimitriou et al, 2005). On the other hand, many papers have documented the use of the subloading surface concept.…”
Section: Stišness and Its Degradation-elasticity And Smooth Transitiomentioning
confidence: 99%
“…The subloading surface concept (Hashiguchi and Ueno, 1977) and the bounding surface concept (Dafalias and Popov, 1975) are the two popular methods that do this. Although use of bounding surface plasticity is widely documented in the broader geomechanics literature, there have been few papers in Soils and Foundations that have used this concept (e.g., Papadimitriou et al, 2005). On the other hand, many papers have documented the use of the subloading surface concept.…”
Section: Stišness and Its Degradation-elasticity And Smooth Transitiomentioning
confidence: 99%
“…Therefore, Yoshimine and Koike (2005) emphasized that establishing a link between different fabrics and structures obtained from various preparation methods in the laboratory and the in situ sedimentation and stress histories is very important from a practical point of view. Papadimitriou et al (2005) reported that such a link could be established by using a plasticity model with the inherent fabric anisotropy scheme, proposed by Dafalias et al (2004). However, more experimental data on the effects of specimen preparation method on the stress-strain behavior of sand under various stress and drainage conditions are needed to improve further modeling.…”
Section: Previous Studiesmentioning
confidence: 99%
“…M c and M e are the slopes of CSLs under compression and extension modes of triaxial. a can be obtained from the image analysis [34]. Alternatively, a can be calculated having CSLs under compression and Figure 11.…”
Section: The Model Predictionsmentioning
confidence: 99%
“…Prediction is obtained from a similar model which was disabled by setting f 1 = 0 (data from Miura et al [6]). extension modes of triaxial by using Equation (55) [34]. e A , and can be determined directly by fitting the test data for the CSLs under the compression and extension modes of triaxial in the e-p plane.…”
Section: The Model Predictionsmentioning
confidence: 99%
See 1 more Smart Citation